2021
DOI: 10.3390/nu13020709
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis Finds Increased Blood Levels of All Forms of Ghrelin in Both Restricting and Binge-Eating/Purging Subtypes of Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is a severe psychiatric condition associated with high mortality and chronicity. The hunt for state, trait, subtyping, and prognostic biomarkers is ongoing and the orexigenic hormone ghrelin and its different forms, acyl ghrelin and desacyl ghrelin, have been proposed to be increased in AN, especially in the restrictive subtype. A systematic literature search was performed using established databases up to 30 November 2020. Forty-nine studies met inclusion criteria for cross-sectional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 104 publications
2
15
0
Order By: Relevance
“…All forms of plasma ghrelin levels are elevated in acute AN [76], and resistance develops to the orexigenic hormone, which is produced by the stomach and acts on the HPA, affecting secretion of gonadotropin-releasing hormone, adrenocorticotropic hormone, and GH. The resultant lack of motivating feeding response to ghrelin, despite hunger sensation, supports an altered reward circuit, which may contribute to both onset and maintenance of AN [77].…”
Section: The Endocrinological and Metabolic Setting Of Anmentioning
confidence: 99%
“…All forms of plasma ghrelin levels are elevated in acute AN [76], and resistance develops to the orexigenic hormone, which is produced by the stomach and acts on the HPA, affecting secretion of gonadotropin-releasing hormone, adrenocorticotropic hormone, and GH. The resultant lack of motivating feeding response to ghrelin, despite hunger sensation, supports an altered reward circuit, which may contribute to both onset and maintenance of AN [77].…”
Section: The Endocrinological and Metabolic Setting Of Anmentioning
confidence: 99%
“…Ghrelin secretion increased during fasting and decreased after eating a normal meal [51,52]. In a recent meta-analysis, all forms of ghrelin were found to increase in patients with acute AN during fasting compared with the healthy controls [53]. The starvation with a low body weight in AN patients at admission might trigger the increase in ghrelin to signal the hypothalamus to stimulate food intake.…”
Section: Discussionmentioning
confidence: 96%
“…A systematic meta-analysis showed that all subtypes of AN lead to an increase in ghrelin levels in the acute/fasting state. After receiving treatment, all AN subtypes had decreased ghrelin levels compared to before the treatment, although still increased compared to healthy controls ( 80 ). These findings make ghrelin a possible biomarker for AN.…”
Section: Ghrelinmentioning
confidence: 99%